Modelling and simulation of nanoscale non-planar double gate metal-oxide-semiconductor field effect transistor - Munawar Agus Riyadi, 1977-; Razali Ismail, supervisor; Fakulti Kejuruteraan Elektrik (2012)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2012